Exploring American Cultural Themes in Language Learning: A Qualitative Analysis of 'Focus 4' EFL Textbook - Flora Amiti (European Scientific Journal, ESJ, 2025)
Learning a foreign language requires both time and dedication. Hence, achieving proficiency in the four language skills definitely necessitates the integration of culturally relevant materials that can enrich the learning process, particularly in developing speaking skills. This study examines an upper-intermediate English as a foreign language textbook utilized at the Medical High School “Gostivari” in Gostivar. While the textbook serves as a crucial teaching resource, its content also significantly shapes the students' learning experiences by addressing topics that contribute to both their academic and personal growth, preparing them for future success. The textbook’s analysis mainly concerns activities related to cultural themes, particularly those related to American culture, thus highlighting the importance of examining how these activities facilitate the development of speaking skills. A qualitative research approach was adopted to analyze the textbook's content and evaluate its cultural relevance. The study reveals that the textbook incorporates a diverse array of culture-related activities, aimed at enhancing students' speaking abilities. These activities not only promote cultural understanding but also provide opportunities for students to practice and refine their spoken language skills in meaningful contexts. The incorporated cultural content can boost student engagement since it introduces relevant and thought-provoking scenarios that encourage active participation in speaking activities.